The day of civil resistance: KGB reaction to events in 1972 - Anušauskas, Arvydas (Genocidas ir rezistencija, 2003)
At the beginning of 1972, in comparison to other cities, Kaunas did not stand out in terms of the number of people persecuted or followed by the KGB, or in terms of any illegal movement. On the other hand, one shall not forget the well–known spirit of the ‘provisional capital’. Hence, the KGB paid Kaunas particular attention, but this did not prevent the self–immolation of Romas Kalanta or the unrest that followed. 14 of May became a day of constant tension and stand–by vigilance for the Soviet security services not only in Kaunas, but throughout Lithuania. The outbreak of youth protests was expected every year, but there was no tragic Kalanta–type catalyst. Not only because of the KGB’s very active negative attitude towards self–immolations, but also because of the unambiguous position of a large part of society towards suicide – whatever the reasons, there were almost none such drastic forms of protest in later years.